Cobalt loaded electrospun poly(ε-caprolactone) grafts promote antibacterial activity and vascular regeneration in a diabetic rat model. (December 2022) - Huang, Ziqi; Zhang, Yuwen; Liu, Ruihua; Li, Yi; Rafique, Muhammad; Midgley, Adam C.; Wan, Ye; Yan, Hongyu; Si, Jianghua; Wang, Ting; Chen, Cuihong; Wang, Ping; et al.
Abstract: Diabetes has been associated with postoperative complications, such as increased risk of tissue infection and impaired tissue repair caused by destabilization of hypoxia-inducible factor-1α (HIF-1α). Consequently, it is imperative to fabricate anti-bacterial and pro-regenerative small-diameter vascular grafts for treating cardiovascular disease in diabetic patients. Herein, we developed electrospun cobalt ion (Co 2+ )-loaded poly (ε-caprolactone) (PCL) microfiber vascular grafts (PCL-Co grafts). The released Co 2+ significantly increased the stabilization of HIF-1α in high-glucose (HG)-treated HUVECs (HG-HUVECs) and macrophages (HG-macrophages). This resulted in enhanced cell migration, nitric oxide production, and secretion of bioactive factors by HG-HUVECs, and polarization of HG-macrophages toward M2 phenotypes in vitro . The Co 2+ also conferred anti-bacterial properties to the grafts, while not perturbing the inherent anti-bacterial activities of HG-macrophages. Following abdominal artery implantation into type 2 diabetes mellitus (T2DM) rats, PCL-Co grafts were evaluated for performance in infection (grafts pre-contaminated with Staphylococcus aureus ) and prophylaxes models (grafts alone). PCL-Co grafts prevented the incidence of subsequent infection in prophylaxes model and effectively inhibited the bacterial growth in the infection model. PCL-Co grafts also significantly enhanced cellularization, vascularization, endothelialization, contractile SMC regeneration and macrophages polarization in both models. Collectively, PCL-Co grafts exhibited the potential to combat infection and improve tissue regeneration under diabetes conditions.